Precise medicine of programmed cell death-1/programmed cell death 1 ligand 1 inhibitor immunotherapy combined radiotherapy for inoperable advanced lung cancer: A protocol for systematic review and meta-analysis. Issue 24 (18th June 2021) - Liu, Gang; Lv, Xiaolan; Ding, Yanling; Guo, Yongbo
Abstract: Background: Programmed cell death-1/programmed cell death 1 ligand 1 (PD-1/PD-L1) inhibitors are a group of immune checkpoint inhibitors immunotherapy for cancer treatment. These immune checkpoint inhibitors are becoming first-line treatments for several types of cancer. Radiotherapy for cancer is a traditional treatment and the therapeutic effect is not satisfactory due to the side effect of chemotherapeutic drugs. This study aims to evaluate the efficacy and safety of PD1/PD-L1 inhibitor immunotherapy combined chemotherapy for inoperable advanced lung cancer. Methods: We will utilize PubMed, PubMed Central, EMbase, Medline, CNKI, WAN FANG Database, and Web of Science to screen eligible studies published from January 1, 2015 to December 30, 2020. Two reviewers will extract data and evaluate the risk of bias independently. The quality of the included studies will be evaluated using the RevMan 5.3 software for data analysis. Results: This review will summarize high-quality evidence of trials to evaluate the precise medicine efficacy and safety of PD1/PD-L1 inhibitor combined radiotherapy for inoperable advanced lung cancer. Conclusions: The findings of the systematic review will provide scientific evidence of the efficacy and safety of PD1/PD-L1 inhibitor combined radiotherapy for inoperable advanced lung cancer to guide the clinician's drug use. Ethics and dissemination: Not applicable. INPLASY registration number: INPLASY202140123. Abstract : Supplemental Digital Content is available in the text